Investigating Earth surface deformation with SAR interferometry and geomodeling in the transborder Meuse–Rhine region - Schlögel, Romy; Owczarz, Karolina; Orban, Anne; Havenith, Hans-Balder (Frontiers in Remote Sensing, 2024)
This study aims at differentiating local and regional ground uplift, and sub-regional subsidence induced by groundwater level drawdown, possibly enhanced across fault structures, as monitored by various Synthetic Aperture Radar Interferometry (InSAR) processing methods. In fact, a buoyant mantle plume under the Eifel may be responsible for the regional ground uplift including the Weser-Geul region (BE) and the South Limburg region (NL)which could negatively affect the area proposed for the future Einstein Telescope. Different InSAR processing techniques are compared to evaluate their limits to track fault structures on a time series of Copernicus Sentinel-1 images while detecting and measuring ground motions based on their phase signature. Results present the overall stable ground of the Euregio Meuse-Rhine region, especially at the Belgian-Dutch border while tectonic activity is observed along the Rhine Graben on the German side. As the current neotectonic activity in the target area was not well known, we perform a spatiotemporal analysis of ground deformation associated with the presence of NW-SE trending normal faults where karst also develops as well as along the Variscan NE-SW trending thrust faults. This work shows that identifying deformation hazards using satellite remote sensing (and connected seismological) techniques is challenging mainly due to the (very) small regional scale deformation, terrain conditions and SAR properties. No matter the general ground stability over the area, some agricultural activities are observed as well as deformation along main infrastructure such as railways. Displacements of millimetric order measured along the faults located near the Gueule valley (BE) are probably related to old mining activities.